Personnel, fund and market viability as factors affecting the publication of learning materials for inclusive education in Nigeria (2016)
Ojeniyi (2002) has observed that Nigeria has the largest commercial publishing in Africa, which has been corroborated by Ike (2004) when he describes Nigerian book publishing industry as vibrant, with perhaps, the largest publishing companies in Africa. There are over 1000 book publishing firms in Nigeria (both registered and unregistered), which further places Nigeria at a comfortable leading position in Africa. Despite its robust publishing industry, none of the numerous publishing companies in Nigeria specialise in the publication of educational materials for the physically challenged. This could be as a result of the fact that Nigerian publishers are faced with challenges bordering on trained personnel, access to capital and availability of market for the published learning materialsfor the physically challenged. Thefact that publishing in Nigeria is profit-driven necessitates that considerations are needed in the decision to publish for the all-inclusive education. This study therefore aims at assessing trainedpersonnel, access to capital and availability of market as factors affecting the publication of learning materials for students with special needs in Nigeria in order to recommend ways to overcome the inherent challenges for the actualisation of the dream of all-inclusive education in Nigeria.